Flexible Control of Urban Development Intensity in Response to Population Shrinkage: A Case Study of Shantou City - Peng Zhang; Hui Pu (Buildings)
This study proposes replacing traditional single-value urban development intensity control with an elastic interval-based approach to address urban development challenges under population shrinkage. It constructs a Floor Area Ratio (FAR) assignment framework guided by “ideal value determination—interval value demarcation—specific value agreement”. The northern central urban area of Shantou City serves as an empirical case. The study, focusing on the conflict between inefficient expansion and population loss, delineates elastic development intensity intervals through multi-dimensional factor analysis: a baseline FAR is determined based on master plan objectives and resource carrying capacity; upper limits are calculated considering transportation and ecological constraints; and lower limits are set according to economic feasibility and social demands, forming a gradient-based control framework. Practically, the study area is divided into differentiated density units, with optimized pathways designed for newly developed, under-construction, and existing plots across multiple scenarios. A multi-stakeholder negotiation mechanism is established to dynamically adapt elastic intervals. Results demonstrate that this method maintains the regulatory authority of master plans while significantly enhancing the adaptability of spatial governance. It provides a theoretical and practical paradigm for balancing regulatory rigidity and flexibility in shrinking cities, offering actionable solutions for vacancy risk mitigation and land-use intensification.